Impact of referral reward program on innovative customers' follow-up e-referral: The moderating role of creative self-efficacy. Issue 3 (3rd June 2019) - Zhang, Depeng; Zhang, Fuli; Liu, Si; Du, Helen S.
Abstract : Purpose: With the rise of customer engagement in online products and services innovation, enterprises are seeking effective referral reward program (RRP) to encourage customers' follow-up electronic-referral (e-referral) behaviors. Therefore, how to stimulate more customers to participate in the RRP is very important to enterprises. However, little empirical work has systemically investigated the impact of RRP on customers' follow-up e-referral, as well as the moderating effects of customers' characteristics. To fill those research gaps, the purpose of this paper is to explore the effects of RRP (particularly, reward amount and reward type) on customers' follow-up e-referral, and the role of creative self-efficacy. Design/methodology/approach: Based on the self-perception theory and the context of online customer innovation, this paper establishes a theoretical model and uses an experiment with 160 participants to test the hypotheses on the role of reward (amount and type) and the moderating effect of creative self-efficacy. Findings: The results of the experiment suggest that both reward amount and reward type in RRP positively impact customers' follow-up e-referral. Furthermore, customers' creative self-efficacy moderates the relationship between rewards and customers' follow-up e-referral. Customers with low creative self-efficacy, reward amount significantly stimulate their follow-up e-referral, but such effect is insignificant when customers' creative self-efficacy is high. In terms of reward type, gift reward has more positive effect on customers' follow-up e-referral when they have high (rather than low) creative self-efficacy, but cash reward has more positive effect on those with low (rather than high) creative self-efficacy. Originality/value: First, based on the self-perception theory, the study clarifies the inconsistent relationship between reward and customers' e-referral and contributes to related research. Second, the study broadens the existing research perspective by introducing creative self-efficacy, which shows interesting and powerful moderating effect but has been ignored in previous studies. Third, the study provides valuable advice on how enterprises design an effective RRP to enhance customers' follow-up e-referral.